2004
DOI: 10.1254/jphs.crj04004x
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements and Electrolytes Homeostasis and Their Relation to Antioxidant Enzyme Activity in Brain Hyperexcitability of Epileptic Patients

Abstract: Abstract. Epileptogenesis is a big challenge. Various experimental and human studies suggested that the homeostasis of trace elements, electrolytes, membrane lipid peroxidation, and antioxidants is crucial for brain function, and they were directly or indirectly implicated as taking part in the pathophysiology of neuronal excitability, neuronal excitotoxicity, and seizure recurrence and its resistance to treatment with antiepileptic drugs (AEDs). In addition, AEDs can also alter the homeostasis of trace elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 92 publications
4
50
0
Order By: Relevance
“…Because epileptic seizures induce neurodegeneration in selected areas of brain it is suspected that metals may be involved in the pathogenesis and progress of epilepsy as well [5].…”
mentioning
confidence: 99%
“…Because epileptic seizures induce neurodegeneration in selected areas of brain it is suspected that metals may be involved in the pathogenesis and progress of epilepsy as well [5].…”
mentioning
confidence: 99%
“…Hyperuricemia has been recently reported among epileptics (untreated and treated) (7,26). Despite controversies regarding uric acid being a risk factor for vascular diseases, uric acid has been implicated in vascular endothelial cell dysfunction.…”
Section: C) Uric Acid Metabolism In Epilepticsmentioning
confidence: 99%
“…The tendency to have recurrent, unprovoked seizures occurs with a prevalence of about 0.5% and a cumulative lifetime prevalence of 3% (1). Many studies have demonstrated that prolonged treatment with antiepileptic drugs (AEDs) could have some undesirable metabolic side effects including elevated plasma concentration of homocysteine (Hcy) (2 -4) and altered serum levels of cholesterol, lipoproteins (5,6), and uric acid (7). These findings have important clinical relevance to vascular endothelial dysfunction and atherosclerosis-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, epilepsy may be associated with neurodegeneration, presumably due to abnormal lipid peroxidation. 1,2 On the other hand, comorbid depression is common in patients with epilepsy. A review of available studies 3 suggested a high prevalence of mood (affective) disorders, especially major depression (8%-48%), followed by anxiety (5%-32%), in patients with epilepsy.…”
Section: Introductionmentioning
confidence: 99%